PENGARUH PROFITABILITAS DAN KOMPENSASI RUGI FISKAL TERHADAP PERENCANAAN PAJAK PADA PERUSAHAAN SUB SEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017–2020 - Meldaria Hutagalung; Harman Malau (Program Studi Magister Manajemen Universitas Advent Indonesia, 2022)
The purpose of this study is to determine whether there is an effect of profitability and fiscal loss compensation on tax planning in the plastics and packaging sub-sector listed on the Indonesian stock exchange for the period 2017-2020. The population of this study is a manufacturing company in the plastics and packaging sub-sector with a sample of as many as 15 companies. The research was conducted using quantitative methods with purposive sampling technique. This study uses secondary data obtained from the financial statements of the plastic and packaging sub-sector companies listed on the Indonesian stock exchange for the period 2017 – 2020. This study uses a sample testing method with the results of the classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation) , hypothesis testing (t test, f test), coefficient of determination test and descriptive statistics. The researcher analyzed the data based on the simultaneous test results that profitability and fiscal loss compensation both had no significant effect on tax planning in plastic and packaging sub-sector companies listed on the Indonesian stock exchange for the 2017-2020 period.